An intervention program based on team building during tactical training tasks to improve team functioning - Tassi, J. M.; López-Gajardo, M. A.; Leo, F. M.; Díaz-García, J.; García-Calvo, T. (Frontiers in Psychology, 2023)
The study aimed to analyze the effects of an intervention program based on team building developed in technical-tactical training tasks in football. Specifically, it examined the benefits of the intervention in variables related to the conceptual model of team building: role clarity, team identification, intra-team communication, cohesion, intra-group conflict, commitment to the team, inside sacrifice, transactive memory systems, collective efficacy, and perceived performance. The participants were 51 young elite footballers divided into an experimental group (n = 27) and a control group (n = 24). The methodological design was quasi-experimental with a duration of 8 weeks. The data were collected three times: pretest, posttest, and follow-up. The results showed differences favoring the experimental group compared to the control group after the implementation of the intervention program in the following variables: team identification (p < 0.001), role clarity (p < 0.001), intra-team communication (p < 0.001; except distinctiveness), group cohesion (p < 0.05), social conflict (p = 0.001), commitment to the team (p < 0.001), inside sacrifice (p < 0.001), transactive memory systems (p < 0.01; except coordination), collective efficacy (p = 0.02) and team performance (p = 0.001). Consequently, the application of team-building strategies incorporated into specific technical-tactical training tasks in football seems to improve group dynamics in sports teams.